Life returns to bird flu ground zero - Orejas, Tonette T. (2017)
People from San Luis, Pampanga are trying to restore normalcy in their poultry-dominated town in the aftermath of the country's first outbreak of avian flu.
Keywords: Avian Influenza A virus -- Pampanga